REGISTER USED BY NOL DERAJAT FILM COMMUNITY IN THE PROCESS OF MAKING REFLECTION MOVIE - DZAKY, ABDI MUFLIH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Register, Sociolinguistics, Process of Making Movie, Community. Register is a variety of language used in particular setting and situation. Certain community uses register for delivering messages between members easily. In this study, the writer investigated the register used in cinematography community come from Universitas Brawijaya named Nol Derajat film when they make Reflection movie. Therefore, this study was conducted to answer the following questions: 1). What are the registers and their meaning used in the process of making Reflection movie by Nol Derajat film community? 2). What are the functional contexts of register found in the process of making Reflection movie by Nol Derajat film community? and 3). What are the factors facilitating the use of the registers?This study used a qualitative approach. The data were utterances which contain register. In collecting the data, the writer used documentation (as the primary instrument) and interview. In data analysis, the writer put the data into a table to define the literal meaning and register meaning. Then, the writer analyze the aspect of functional context which consist of field, mode and tenor using Halliday and Hasan’s (1985) theory and analyzed the factor facilitating the use of register using Yule’s (2006) theory.The result of this study revealed that there were 20 registers used in the process of making movie. They are Action, bocor, camera, choose, clipper, cut, detail, focus, freeze, in-frame, lighting, longshot, noise, reflector, rolling, scene, shot, sound, take, and talent. All those registers have 2 different meanings namely literal meaning and register meaning. The writer found the field and the tenor of all utterances different due to different topic and speaker in each conversation.However, the mode of all utterances is the same that is spoken language. Then, thewriter found the factor facilitating the use of those registers that is the context of the sentence. The context was divided into situational context (shooting location), occupational (among filmmaker), and topical (talking about something importantin making movie).For further study in register, the writer suggests that the next writers who want to conduct a study on register phenomena analyze it in other communities, such as photography community and use different technique, such as key person technique. Lastly, the next writer may apply different theories from other linguistics field in analyzing the finding so the result can be richer and more various.